Validation of the 2H-SNIF NMR and IRMS Methods for Vinegar and Vinegar Analysis: An International Collaborative Study - Federica Camin; Marco Simoni; Armin Hermann; Freddy Thomas; Matteo Perini (Molecules, 2020)
This paper presents the results of a collaborative study involving seven laboratories and concerning two samples of wine vinegar, one of apple vinegar and four of balsamic vinegar. The aim of the study was to define standard deviations of repeatability (sr) and reproducibility (sR) for vinegar and balsamic vinegar stable isotope ratios of H (D/H), C (δ13C) and O (δ18O), in order to establish them as fully recognized official standards. Acetic acid was extracted and subjected to (D/H)CH3 and δ13C analysis. δ18O analysis was performed on whole samples. The grape must solution remained after distillation of balsamic vinegar was fermented and the resulting ethanol was subjected to (D/H)I, (D/H)II, R and δ13C analysis. The sr and sR were 0.6 ppm and 1.1 ppm for (D/H)CH3, 0.14‰ and 0.25‰ for δ13C of acetic acid, 0.1‰ and 0.17‰ for δ18O of water, 0.19 ppm and 0.64 ppm for ethanol (D/H)I, 1.14 and 1.31 ppm for (D/H)II, 0.09 and 0.11‰ for δ13C of ethanol. These data are in line with those in the literature or reported in corresponding official methods, and sr and sR of balsamic vinegar are in line with those of vinegar and must.